Innovation Diffusion Perspective on Digital Transformation in Education: Toward A Smart School System - Lulu Waliyatur Rosyida; Nur Rahmi Sonia (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
Digital transformation refers to a comprehensive process of change encompassing educational systems, organizational culture, strategies, and governance. The success of the transformation toward a smart school system depends not only on the availability of technology, but also on the acceptance and adoption of innovation by all members of the school community. This study aims to examine digital transformation in education from the perspective of innovation diffusion theory in realizing a smart school system. This research employs a Systematic Literature Review (SLR) method based on the PRISMA framework, analyzing ten scientific articles and relevant academic sources published between 2021 and 2026. Data were obtained from Scopus, Sinta-indexed journals, and Google Scholar databases. The data were analyzed using a thematic analysis approach to identify patterns, determinants of innovation adoption, and conceptual synthesis for developing a smart school system based on the innovation diffusion perspective. The findings indicate that the success of digital transformation in schools is influenced not only by technological availability but also by innovation characteristics, human resource readiness, digital leadership, and organizational support. This study implies that a digital transformation model based on innovation diffusion can serve as a conceptual framework for building an educational system that is adaptive to technological change. Future research is recommended to develop empirical studies testing the innovation diffusion based digital transformation model at various educational levels and institutional contexts, as well as exploring the integration of emerging technologies such as artificial intelligence in developing smart school systems.